Urodynamic assessment and proteomic analysis of lower urinary tract dysfunction following nerve-sparing radical hysterectomy - Tsuyoshi Majima; Yoshihisa Matsukawa; Yasuhito Funahashi; Keishi Kajikawa; Momokazu Gotoh; Naoto Sassa (Scientific Reports)
Abstract This study aimed to evaluate lower urinary tract dysfunction after radical hysterectomy using urodynamic studies and to identify urinary biomarkers for detrusor underactivity via proteomic analysis. This prospective single-center study included women who underwent nerve-sparing radical hysterectomy for cervical carcinoma. Preoperative and postoperative assessments (at 1 and 6 months) included the International Prostate Symptom Score (IPSS), Overactive Bladder Symptom Score, urethral pressure profiling, and pressure flow studies. Detrusor contractility was assessed using the projected isovolumetric pressure (PIP1). Proteomic analysis was performed to identify urinary biomarkers associated with postoperative detrusor underactivity. Twenty-five patients were included. The total IPSS increased significantly at 1 and 6 months postoperatively. The maximum urethral closure pressure decreased significantly at 1 month and stabilized thereafter. PIP1 and voiding efficiency decreased significantly at 1 month, but improved by 6 months. Proteomic analysis revealed significant correlations between the changes in urinary ezrin, moesin, transthyretin, and PIP1 levels. Receiver operating characteristic analysis identified the optimal cutoff values for these biomarkers in diagnosing detrusor underactivity (PIP1 < 30). It was concluded that nerve-sparing radical hysterectomy impairs detrusor contractility and urethral function. Additionally, urinary ezrin, moesin, and transthyretin levels may be valuable biomarkers for diagnosing detrusor underactivity.